Comparison study of combination of cryotherapy & intralesional injection and multipuncture of bleomycin vs cryotherapy in resistant palmoplanter warts - Mehdi Amirnia; Mohamad Ranjkesh; Mir ahad Mousavi (مجله پزشکی دانشگاه علوم پزشکی تبریز, 2021)
Background: Although many warts are treated with usual methods, resistant cases are common problems. Bleomycin is one of the drugs used for resistant cases. The aim of this study was to compare the effect of cryotherapy and intralesional bleomycin injection combination with cryotherapy in the treatment of resistant warts. Methods: Sixty patients with resistant warts were selected and randomly divided into two groups of 30 A and B patients. In each group, cryotherapy was performed three sessions during 0, third and, sixth weeks in case of visible lesions. In group B, in addition to cryotherapy in week 0, and in the presence of visible lesions during week 3, injections of intra-lesions of bleomycin 1 mg/ml were administered. Treatment outcomes and possible complications were evaluated during the third and sixth weeks. Results: The response to the treatment was defined as poor, moderate, and well by the physician, which was 16.7%, 53.3% and, 10% in group A after 3 weeks of treatment, respectively and was 16.7%, 50% and, 33.3% in group B, respectively. The response to the treatment after 6 weeks of treatment was 33.3%, 40%, and 26.7% in group A and was 6.7%, 40%, and 53.3% in group B, respectively. Conclusion: Combined treatment of cryotherapy and intralesional bleomycin injection is more effective than cryotherapy in the treatment of resistant warts.